Pengaruh Ukuran Perusahaan dan Umur Perusahaan terhadap Pengungkapan Sumber Daya Manusia (Studi Empiris pada Perusahaan yang Terdaftar di LQ-45 Tahun 2017) - Agus Waloya (Universitas Islam Negeri Raden Mas Said Surakarta, 2018)
AbstractThis study aims to analyze the effect of company size and company age on disclosure of human resources in companies listed on the LQ45 stock index in 2017. By using a quantitative approach, the hypothesis test in this study was tested using multiple linear regression analysis. The total sample in this study were 39 companies. The results of this study indicate that the size and age of the company does not affect the disclosure of human resources. Keywords: frm size, frm age, human resources disclosure